Effects of melatonin and memantine administration on the learning and memory performances of hypoxic juvenile rat pups - Elibol, Birsen; Şahbaz, Çiğdem; Eyüboğlu, Siğnem; Çevreli, Burcu; Kılıç, Ülkan; Kılıç, Ertuğrul (Yerküre Tanıtım ve Yayıncılık Hizmetleri A.Ş., 2020)
Objective: Herein, we aimed to investigate the long-term effects of neonatal hypoxia and the potential protective role of melatonin and memantine on the learning and memory. Methods: Seven-day-old rat underwent right carotid ligation, followed by hypoxia. Rat received Melatonin (MLT) (4 mg/kg), Memantine (MEM) (20 mg/kg), and MLT+MEM combination after hypoxia. We tested these rats for anxiety by elevated O-maze and for spatial learning and memory by Morris water maze (MWM) at postnatal day 45. Results: Hypoxia increased the level of anxiety compared to the control group (p=0.05) while treatment of MLT, MEM, and MLT+MEM ameliorated this effect. In addition, hypoxia produced significant decrease in spatial learning of the rats on the fourth day of training (P=0.05) and the percent time spent in the platform quadrant and the entrance frequencies to the platform quadrant compared to the control group (P=0.049 and P=0.023). Treatment of MLT, MEM, and MLT+MEM after hypoxia improved the performance of the rats at the third (P=0.686, P=0.876, P=0.977, respectively) and fourth day (P=0.738, P=0.553, P=0.789, respectively) of MWM training. The decrease in the percent time spent was ameliorated by the treatment of MLT (P=0.239), MEM (P=0.289), and MLT+MEM (P=0.567) compared to the control group. In addition, MLT treatment significantly increased the entrance frequency to the platform quadrant compared to the hypoxia group (P=0.020). Conclusion: Our data suggested that the MLT was more effective in the release of memory deficits from hypoxia-related damage. MLT might have a therapeutic value in improving hypoxic damage in the developing brain.
Keywords: Neonatal Hypoxia; Learning and Memory; Melatonin; Memantine; Morris Water Maze